(3JbQjQGJ MHjH Gddg GdQTJjs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg (B... (3bhdg cJGH GdQgf hGdfXQ ajg jSJOYj aUhdG ; GdChd aj GdQgf hgh hKjbI dOjf GdeQJgf , GdcJGH bO jWdb Ydi GdeYfi GdeUOQj hgh UaI bGFeI HGdehUha hbO jWdb Ydi GdecJhH (B...s
(3BNQgG (B:s
... (3dh UGQ GdQGgf gh GdSHH aj (B... (3eG PcQhg ef YhO GdQgGfI dCf GdYGFO CbQH dGHOGd aj GdZQGeI aJYjf HOdG Yf GdYUjQ GdJGda Gddge EdG Gf jKHJ HeG GOYjfG ef HbGA GdYdI (B.. (3gPG eG JjSQ aj HGH GdQgfs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis